A new amphipod Nicippe rogeri sp. nov. (Crustacea, Pardaliscidae) from New Zealand’s deep sea - Lörz, Anne-Nina; Schnabel, Kareen (Zootaxa, 2015)
The amphipod family Pardaliscidae has a worldwide distribution and is considered to be especially common in the deep sea. This is the first record of the genus Nicippe in New Zealand waters and a new species, N. rogeri sp. nov is described in honour of Dr. Roger Bamber. This brings the number of species in the genus Nicippe worldwide to four. The new species is described in detail and a key to the four species of Nicippe is provided.